Crocus sativus L. (Saffron) Stigma Aqueous Extract Induces Apoptosis in Alveolar Human Lung Cancer Cells through Caspase-Dependent Pathways Activation. (29th October 2013) - Samarghandian, Saeed; Borji, Abasalt; Farahmand, Seyed Kazem; Afshari, Reza; Davoodi, Saeideh
Abstract : Worldwide, lung cancer is the most common form of cancer. Saffron has been used in folk medicine for centuries. We investigated the potential of saffron to induce cytotoxic and apoptotic effects in lung cancer cells (A549). We also examined the caspase-dependent pathways activation of saffron-induced apoptosis against the A549 cells. A549 cells were incubated with different concentrations of saffron extract; then cell morphological changes, cell viability, and apoptosis were determined by the normal invertmicroscope, MTT assay, Annexin V and propidium iodide, and flow cytometric analysis, respectively. Activated caspases were detected by treatment of saffron in lung cancer cells using fluorescein-labeled inhibitors of polycaspases. The proliferation of the A549 cells were decreased after treatment with saffron in a dose- and time-dependent manner. The percentage of apoptotic cells increased with saffron concentrations. Saffron induced morphological changes, decreased percentage of viable cells, and induced apoptosis. Saffron could induce apoptosis in the A549 cells and activate caspase pathways. The levels of caspases involved in saffron-induced apoptosis in the A549 cells indicating caspase-dependent pathway were induced by saffron. The anticancer activity of the aqueous extract of saffron could be attributed partly to its inhibition of the cell proliferation and induction of apoptosis in cancer cells through caspase-dependent pathways activation.